Impact of contrasting tillage, residue mulch and nitrogen management on soil quality and system productivity under maize-wheat rotation in the north-western Indo-Gangetic Plains - Adak, Sujan; Bandyopadhyay, Kalikinkar; Purakayastha, Tapan Jyoti; Sen, Suman; Sahoo, Rabi Narayan; Shrivastava, Manoj; Krishnan, Prameela (Frontiers in Sustainable Food Systems, 2023)
The sustainability of dominant rice-wheat rotation is under threat due to numerous water-, nutrients-, weeds-and environment-related problems, mainly, due to rice cultivation in north-western Indo-Gangetic Plains (NWIGP) of India. It needs crop-and soil-appropriate management techniques with a focus on conservation agriculture (CA) that, which can maintain soil health which in turn is essential for long-term is of the utmost essential for sustainability of intensive cereal-based cropping system. Thus, rice-wheat rotation may be diversified withby using Formatted: Highlight maize as feasible substitute for rice. But, there is a dearth of comprehensive investigation on the impact of short-term CA in maize-wheat rotation, on soil quality. Hence, an attempt has been made to assess the system productivity and soil quality in a four-year-old CA-based maize-wheat rotation.: Contrasting tillage as the main plot [Conventional tillage (CT), No-tillage (NT)], crop Methods: Contrasting tillage as the main plot [Conventional tillage (CT), No-tillage (NT)], crop residue mulch as subplot (residue mulch (M+), no residue (M0)),and nitrogen (50 (N1), 100 (N2), 150% (N3) of recommended nitrogen dose) as sub-sub plot were laid out in split-split plot design. Soils sampled from 0-0.05, 0.05-0.15, and 0.15-0.30 m soil layers were examined to develop a unified soil quality index (SQI) . The available K, P, total organic carbon (TOC), EC, bulk density (BD), dehydrogenase activity (DHA), and soil microbial biomass C (SMBC) were identified as the crucial "minimum data set" for SQI using PCA.Results: Results showed that, NT and M+ plots had 10.52 and 17.39% higher mean weight diameter (MWD) than CT and M0, respectively. NT and M+ plots increased TOC by 5.26 and 8% than CT and M0 plots, respectively in 0-0.05 m soil layer. Available K and P were found to be significantly higher in M+ plots than that of M0. The highest and lowest SQI was registered with NTM+N3 and CTM0N1, respectively. SP was significantly and positively correlated with SQI. Diversification of rice-wheat system with maize-wheat rotation following CA practices appears to have a positive impact on soil health. Therefore, CA-based maize-wheat rotation may be recommended to improve soil quality and system productivity in NWIGP region.